UNDERSTANDING THE ECONOMIC IMPACT OF TOURISM IN THE ASIAN PACIFIC REGION USING THE TOURISM SATELLITE ACCOUNT (TSA) - DAVID MC.A BAKER (Centre For Tourism Planning and Development, 2013)
Tourism is increasingly a major aspect of the global economy, the global market share of the Asian and Pacific region increased from 15.7 per cent in 1996 to 19.8 per cent in 2006.With the growing recognition of tourism as a source of employment generating growth in the countries, improved understanding of what tourism is, its role in the economy and its relationship to other parts of the economy is important. The Tourism Satellite Account (TSA) is a new framework recently adopted by the United Nations Statistical Commission that provides an important platform towards forging improved understanding of the structure and role of tourism in the economy. Estimates using the TSA framework have the advantage of being credible, with the methodology now widely accepted, and internationally comparable. In the Asian and Pacific countries, the development of the Tourism Satellite Account (TSA) is an important step in obtaining world recognition and support. The aim of this study is to analyze how the TSA conceptual framework is working in the Asia Pacific region with particular attention to the measurement of the economic importance of the industry. The focus is on the use and analysis of TSA in different countries. In this study the survey method was used along with secondary reports, results indicate that a number of countries have already been using the TSA or in the process of initiating its use. Challenges include deficiencies in the information base, major gaps in the data and weaknesses in the comprehensiveness of otherwise useful sources, further implications regarding the TSA are identified.